2019
DOI: 10.29015/cerem.781
|View full text |Cite
|
Sign up to set email alerts
|

The Seven Sustainability Competences according to the RESFIA+D Model

Abstract: Aim:The article describes the origins, structure and applications of a model for professional competences for sustainable development, called RESFIA+D. The model provides an assessment and policy instrument that can easily be applied practically.Companies, NGO’s and other organizations may apply RESFIA+D as a structured tool for human resource development (HRD). Institutions for higher and vocational education can use the instrument for education (re)development, where curricula and didactic approaches are der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Throughout these phases, to date, there is a long research background demonstrating the interest that the scientific community has shown around the revision and establishment of the conceptual and methodological bases of ESD in the university scope (Amaral et al, 2015;Caride and Meira 1998;Ferrer-Balas, Buckland, and De Mingo 2009;González-Gaudiano 2005;González-Gaudiano and De Alba-Ceballos 1994;Leal-Filho 2011;Lele 2017;Limón 2006;Lozano et al 2015;Novo 2009;Tilbury 1995;Waas, Verbruggen, and Wright 2010;Wright 2002;2006;Xiong et al, 2013) and the development of specific research lines, such as environmentalisation and/or curricular sustainability (Junyent and de Ciurana 2008;Watson et al 2013;Wemmenhove and de Groot 2001), faculty training (Aznar et al 2018;Calafell and Junyent 2017;Gough 2016;Solis-Espallargas and Valderrama-Hernández 2015), the establishment of key competences (García-Esteban and Murga-Menoyo 2015;Roorda 2019;Sánchez Carracedo et al 2018;Sims and Falkenberg 2013;Vare et al 2019;Wiek, Withycombe, and Redman 2011), and the implementation of sustainability approaches, methodologies and projects carried out in the university scope (Aramburuzabala, Cerrillo, and Tello 2015;Tamura and Uegaki 2012), as is reflected in the bibliometric analyses performed (Alcalá del Olmo-Fernández et al 2021;Toscano, Fuentes, and Fajardo 2019) and the extensive literature in this respect. Likewise, it is of necessary reference to create networks in the different regions of the world, together with the commitment and work that has been developed since the 1990s with respect to the inclusion of s...…”
Section: Justificationmentioning
confidence: 99%
“…Throughout these phases, to date, there is a long research background demonstrating the interest that the scientific community has shown around the revision and establishment of the conceptual and methodological bases of ESD in the university scope (Amaral et al, 2015;Caride and Meira 1998;Ferrer-Balas, Buckland, and De Mingo 2009;González-Gaudiano 2005;González-Gaudiano and De Alba-Ceballos 1994;Leal-Filho 2011;Lele 2017;Limón 2006;Lozano et al 2015;Novo 2009;Tilbury 1995;Waas, Verbruggen, and Wright 2010;Wright 2002;2006;Xiong et al, 2013) and the development of specific research lines, such as environmentalisation and/or curricular sustainability (Junyent and de Ciurana 2008;Watson et al 2013;Wemmenhove and de Groot 2001), faculty training (Aznar et al 2018;Calafell and Junyent 2017;Gough 2016;Solis-Espallargas and Valderrama-Hernández 2015), the establishment of key competences (García-Esteban and Murga-Menoyo 2015;Roorda 2019;Sánchez Carracedo et al 2018;Sims and Falkenberg 2013;Vare et al 2019;Wiek, Withycombe, and Redman 2011), and the implementation of sustainability approaches, methodologies and projects carried out in the university scope (Aramburuzabala, Cerrillo, and Tello 2015;Tamura and Uegaki 2012), as is reflected in the bibliometric analyses performed (Alcalá del Olmo-Fernández et al 2021;Toscano, Fuentes, and Fajardo 2019) and the extensive literature in this respect. Likewise, it is of necessary reference to create networks in the different regions of the world, together with the commitment and work that has been developed since the 1990s with respect to the inclusion of s...…”
Section: Justificationmentioning
confidence: 99%
“…This can be easily assured during the execution of the project up to a specific point in time by understanding the customer's needs and converting them into project service specifications. Critical success factors are the critical factors needed to achieve the project goals and are essentially static (Roorda, 2019). Naeem, et al (2018) have considered a challenge plan to achieve the challenge through an intermediate position in hazard control and a coordinated position in corporate culture.…”
Section: Literature Reviewmentioning
confidence: 99%